Comparison Analysis of ASEAN Banking Financial Performance During the Pandemic - Justita Dura (Universitas Medan Area, 2022)
The arrival of the Covid-19 Pandemic outbreak has had an impact on the collapse of the local economy. The macroeconomics used in this theory explains the relationship between the current economic situation and how it affects banking financial performance with the RGEC indicators were used in this study to compare the financial performance of Indonesia's banking sector with other ASEAN countries, such as Brunei Darussalam, Malaysia, Myanmar, the Philippines, Singapore, Thailand, and Vietnam. This research is a component of comparative research. The subject of the study is ASEAN banking institutions. Sampling with the purposive sampling method in 2019 and 2020 obtained 13 banks produced a complete sample. The parametric homogeneity test is used to test hypotheses in statistical models. The findings show that although there were differences in profit risk and risk profiles of ASEAN banks during the pandemic, there was no difference in capital risk.